2021
DOI: 10.47892/rgp.2021.413.1154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de síndrome de intestino irritable en América Latina

Abstract: El síndrome de intestino irritable es una enfermedad funcional intestinal frecuente a nivel mundial, pero con pocos estudios de prevalencia. Su diagnóstico es clínico y se basa en criterios acordados internacionalmente que han cambiado con el tiempo, actualmente regidos por el Consenso de Roma IV. Objetivo: Recabar y actualizar datos disponibles de prevalencia de América Latina para entender mejor el comportamiento regional de SII. Materiales y métodos: Se realizó una búsqueda de trabajos originales, autodefin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
5
1
4
Order By: Relevance
“…Nevertheless, this is slightly higher than the average total prevalence reported for IBS in the general population in Latin America, which was estimated at 15.4% (Rome II criteria 23.5%; Rome III 11.8%; and Rome IV 6.98%) (10). The prevalence of the present study reflects a superiority compared to another study conducted in human medicine students from a university in Peru, using the Rome III criteria, in which the prevalence of IBS was 12.4% (29).…”
Section: Prevalence Of Ibsmentioning
confidence: 54%
See 1 more Smart Citation
“…Nevertheless, this is slightly higher than the average total prevalence reported for IBS in the general population in Latin America, which was estimated at 15.4% (Rome II criteria 23.5%; Rome III 11.8%; and Rome IV 6.98%) (10). The prevalence of the present study reflects a superiority compared to another study conducted in human medicine students from a university in Peru, using the Rome III criteria, in which the prevalence of IBS was 12.4% (29).…”
Section: Prevalence Of Ibsmentioning
confidence: 54%
“…However, the average prevalence of IBS for Latin America was 15.4%; furthermore, according to Rome II, III, and IV criteria, the prevalence of IBS was 23.5, 11.8, and 6.98%, respectively (10). Multiple factors have been proposed that influence the increase in IBS prevalence (4), such as bacterial etiology, psychological components (stress, anxiety, and/or depression), social and academic factors, female gender (11), and disorders in eating behavior (7).…”
Section: Introductionmentioning
confidence: 95%
“…Egypt had the highest prevalence rate of internet surveyed countries[ 8 ]. As well as that, representative researches have also been carried out in various countries in recent years and reported that the prevalence of IBS was 5.2% (Rome IV), 5.9% (Rome III), and 6.98% (Rome IV) in Gibraltar, the United Kingdom[ 9 ], Hangzhou, China[ 10 ] and Latin America[ 11 ], respectively. Based on population survey data in the United States, Canada, and the United Kingdom, the results revealed the Rome III IBS rate was roughly twice as high as the Rome IV rate[ 12 ].…”
Section: Regionalization Should Be Emphasized In Epidemiologymentioning
confidence: 99%
“… 2 Among medical students, this rate escalates to 30.9% to 36.3%. 3 , 4 In Latin America, its prevalence ranges from 3% to 25%, with Peru reporting a rate of 21% for its general populace 3 , 5 and 9.5% to 12.4% among medical students. 4 , 6 The pivotal role of IBS is endothelial dysfunction resulting from chronic inflammation, predisposing individuals to vascular risks and consequently erectile dysfunction (ED) caused by impaired nitric oxide availability from inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%